Pendampingan Kelembagaan Desa Tangguh Bencana (Destana) pada Desa Rawan Bencana Banjir Lahar Dingin Gunung Kelud di Kecamatan Kasembon - Syarif Hidayatullah; eko aristanto; umu khouroh; irany Windhyastiti; Andi Nu Graha (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2020)
This service activity aims to help institutional strengthening of the Tangguh Disaster Village (Destana) in disaster planning at the village level in the context of increasing preparedness and overcoming the cold lava flood disaster. The activity was carried out in Kasembon Subdistrict with an implementation time of 3 months. The target groups for this activity are village officials, management and members of the disaster management forum, tagana volunteers and informal leaders from Bayam Village, Pondokagung Village and Pandansari Village. The method of implementing this activity is training and assistance with 6 stages of activities including: i) coordination and outreach, ii) participatory community FGDs, iii) disaster management training, iv) tracking disaster-prone areas, v) mentoring in preparing village disaster documents, vi) evaluation implementation of activities. The results of the implementation of the dedication showed that the attendance rate of participants was 86.7%, the participation rate was 80%, the level of understanding of training materials was 73.3%; and the completion rate of disaster documents by 100%. The main output of this activity is the Gunung Kelud Cold Flood Lava Contingency Plan Document for Bayam Village, Pondokagung Village and Pandansari Village.